Caffeine, Fluid-Electrolyte Balance, Temperature Regulation, and Exercise-Heat Tolerance - Armstrong, L. E.; Casa, D. J.; Maresh, C. M.; Ganio, M. S. (Exercise and Sport Sciences Reviews, 2007)
Dietitians, exercise physiologists, athletic trainers, and other sports medicine personnel commonly recommend that exercising adults and athletes refrain from caffeine use because it is a diuretic, and it may exacerbate dehydration and hyperthermia. This review, contrary to popular beliefs, proposes that caffeine consumption does not result in the following: (a) water-electrolyte imbalances or hyperthermia and (b) reduced exercise-heat tolerance.